An assessment of the Coulter counter model S - Pinkerton, P. H. (1970)
An assessment of the Coulter model S automatic blood counter has been carried out. The standard deviations for the haemoglobin concentration, haematocrit, red cell count, and white cell count are, respectively, ± 0·15 g/100 ml, ± 0·45%, ± 0·04 m/c mm, and ± 0·47 thous/c mm. These results are clearly more accurate than careful manual estimates, performed for comparison on the same samples. Details of the comparisons are presented. A comparison is also made with routine daily estimations. `Carryover' from one sample to the next was found to be about 2%, and tests in the ranges likely to be found in practice showed good linearity for the haemoglobin estimation, haematocrit, red cell count, and white cell count. A brief account of instrument failures is given. The performance of the Coulter model S compares well with that of other automated equipment for which detailed evaluations are available.